2014
DOI: 10.5539/ass.v10n6p107
|View full text |Cite
|
Sign up to set email alerts
|

Addictive Facebook Use among University Students

Abstract: The Facebook has become an essential part of almost every university students daily life.Comment: 10 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 49 publications
(58 reference statements)
4
52
0
6
Order By: Relevance
“…In general, it seems as though Facebook is commonly used as a tool to procrastinate or distract from important tasks. Similar themes also emerged in a small qualitative study on Facebook addiction (Zaremohzzabieh, Samah, Omar, Bolong, & Kamarudin, 2014).…”
Section: Negative Consequencesmentioning
confidence: 70%
See 1 more Smart Citation
“…In general, it seems as though Facebook is commonly used as a tool to procrastinate or distract from important tasks. Similar themes also emerged in a small qualitative study on Facebook addiction (Zaremohzzabieh, Samah, Omar, Bolong, & Kamarudin, 2014).…”
Section: Negative Consequencesmentioning
confidence: 70%
“…This result was expected, given that the recruitment advertisements asked for participants who felt that they spent too much time on Facebook. Furthermore, Zaremohzzabieh et al (2014) reported that excessive Facebook users were personally aware of their high frequency of use. In general, responses coded within this theme simply acknowledged that the individual was aware that they use Facebook too much.…”
Section: Excessive Usementioning
confidence: 99%
“…Thus far, many studies of problematic SNS use have focused specifically on Facebook (e.g., Hong, Huang, Lin, & Chiu, 2014;Zaremohzzabieh, Samah, Omar, Bolong, & Kamarudin, 2014). This is unsurprising, considering the high proportion of Facebook use compared to other forms of SNSs.…”
Section: Introductionmentioning
confidence: 92%
“…In one qualitative study of problematic Facebook users, a female respondent admitted that limiting her Facebook checking to once a day left her feeling overwhelmed with information (Zaremohzzabieh et al, 2014). As a result, she spent most of her time checking Facebook for updates in order to more efficiently monitor what was happening with her friends.…”
Section: Future Research: Pathways To Problematic Facebook Usementioning
confidence: 99%
“…Similarly, past gratifi cations studies (e.g. Zaremohzzabieh et al, 2014) identifi ed signifi cantly positive association between SNSs motivations and the amount of time (duration) which users' spend on SNSs. However, the infl uence of frequency and duration on users' attitude towards SNA as well as on their behavior to click on ads appearing on SNSs is still unaddressed.…”
Section: Introductionmentioning
confidence: 99%